Analisis Teologis Fintech terhadap Etika Keuangan Keluarga Sederhana Berbasis Gereja Kontemporer - Elisa Nimbo Sumual; Yohana Fajar Rahayu (STT INDONESIA MANADO, 2026)
Abstract: Abstract: This study aims to analyse, from a theological perspective, the impact of developments in financial technology on the financial ethics of ordinary families within the context of the contemporary church, with an emphasis on the integration of faith and economic practice. The methodology employed is descriptive qualitative, utilising a contextual theological approach and Christian ethical analysis based on a review of the literature. The research findings indicate that fintech offers ease of access and financial efficiency, yet it also fuels consumerist behaviour, digital debt dependency, and a weakening of family financial discipline. On the other hand, the church has not yet responded optimally to these changes through systematic and contextual financial ethics education. The integration of Christian economic theology, family ethics and fintech literacy is crucial in fostering critical awareness amongst the congregation. The study’s conclusion emphasises that the church needs to develop a faith-based financial education model that is adaptive, reflective and transformative to strengthen stewardship and the economic stability of families in the digital age. Abstrak: Penelitian ini bertujuan menganalisis secara teologis dampak perkembangan teknologi finansial terhadap etika keuangan keluarga sederhana dalam konteks gereja kontemporer, dengan menekankan integrasi antara iman, praktik ekonomi. Metode yang digunakan adalah kualitatif deskriptif melalui pendekatan teologi kontekstual dan analisis etika Kristen berbasis studi literatur. Hasil penelitian menunjukkan bahwa fintech menghadirkan kemudahan akses dan efisiensi keuangan, namun juga memicu perilaku konsumtif, dan ketergantungan utang digital, serta melemahnya disiplin finansial keluarga. Di sisi lain, gereja belum optimal merespons perubahan ini melalui pendidikan etika keuangan yang sistematis dan kontekstual. Integrasi antara teologi ekonomi Kristen, etika keluarga, dan literasi fintech menjadi penting dalam membentuk kesadaran kritis jemaat. Kesimpulan penelitian menegaskan bahwa gereja perlu mengembangkan model edukasi keuangan berbasis iman yang adaptif, reflektif, dan transformatif untuk memperkuat penatalayanan serta stabilitas ekonomi keluarga di era digital.